FRI0065 Presence, Grade and Location of Power Doppler Predict Progression of Radiographic Damage in TNFα Blocker Induced Clinical Remission in Rheumatoid Arthritis Patients. (15th July 2016) - Raffeiner, B.; Grisan, E.; Rizzo, G.; Botsios, C.; Doria, A.; Ometto, F.; Punzi, L.
Abstract : Background: Functional outcome of patients with rheumatoid arthritis (RA) depends from control of disease activity and arrest of radiographic damage. Clinical remission can be achieved in the majority of RA patients by combinations of steroids, DMARDs and TNFα blockers. Recent imaging studies identified residual subclinical inflammation in many patients in treatment with DMARDs: active synovitis was demonstrated by magnetic resonance imaging (MRI) and ultrasound (US). Power Doppler (PD) positivity correlated best with radiographic progression (1). On the other hand, TNFα blockers are much more efficacious in blocking radiographic damage by direct inhibition of osteoclasts, but it is not known if PD positivity predicts on-going damage also in RA patients in remission by TNFα blockers. Objectives: To determine the usefulness of PD study to predict structural damage in patients considered in clinical remission by TNFα blocker therapy. Methods: A prospective observational study was performed on 121 consecutive RA patients in therapy with TNFα blockers and in DAS28 remission since 6 months. At baseline US examination was performed in all patients on the metacarpophalangeal, proximal interphalangeal, wrist and metatarsophalangeal joints. Active synovitis was identified by PD positivity. Semi-quantitative PD scoring 0–3 and number of positive joints were registered. The location of PD was scored as follows: capsular and within synovia without bone contact (location 1) or with bone contact and penetrating bone cortex (location 2). At baseline and after one year X-rays of hands and feet were executed. Radiographic progression was expressed as difference in total Sharp Score modified by van der Heijde (ΔTSS) >0. Risk ratios for presence, grade and location of PD relative to radiological progression were calculated. Results: Among the 121 patients, 62 (51, 3%) showed no PD signal at the time of remission, whereas 59 (48, 7%) had PD signal: in 57, 6% of cases grade was 1, in 23, 7% grade 2 and in 18, 6% grade 3. 38 patients showed PD positivity in one joint, 21 in more joints. Among all PD positive joints 92, 4% were at the level of the hands. 74, 6% of PD signals were in contact with articular bone surface (location 2). All patients without PD signal did not show radiographic progression. 28, 8% of patients showing PD positivity (corresponding to 14% of all patients in clinical remission) underwent radiographic progression. Radiographic progression occurred in 20, 6% of patients with PD grade 1, 42, 8% with grade 2 and 36, 3% with grade 3. Whereas only 6, 6% of patients with PD in location 1 progressed, 36, 3% of patients with PD in location 2 showed deterioration of radiographic damage. Despite presence of PD, higher PD grades (2 and 3) and PD with contact to bone surface (location 2) determined a significantly increased risk for radiographic progression; PD in location 1 resulted protective. Conclusions: PD demonstrated to be very useful in evaluating patients considered in remission. Absence of PD signal guarantees arrest of radiological progression, whereas patients with PD signal are at risk for progression despite TNFα blockers. This risk increases with higher PD grades and with PD in contact or penetrating bone profile. References: Brown AK. Arthritis Rheum 2006, 54:3761–73 Disclosure of Interest: None declared